Estimation of height of adult malays attending Hospital Universiti Sains Malaysia (HUSM) using calcaneus bone measurement on plain radiograph - Musa, Ahmad Tarmizi (2014)

(untitled)
Introduction In medico-legal forensic investigation, establishing personal identity of a victim is important. Stature reconstruction is important in providing estimated height of a person from their skeletal remains. Population specific regression equations for stature estimation need to be establishing from the identical bone. Long bone measurement had been used in stature estimation with proved accuracy in many previous studies. With the rise of violence in major cities and mass disaster occurring around the world resulting dismembered human parts and long bones, there was a need for derivation equation from the small bone or long bone fragment for stature estimation. Stature estimation from the regression analysis from the calcaneus measurement had been done by Bidmos which showed significant correlation coefficient and low SEE value. However there is no such study performed with Malay population. Objective To estimate the height of individual Malay adult attending Hospital Universitie Sains Malaysia based on the measurement of calcaneus bone on plain radiograph. Methods These studies have 68 volunteers for underlying lateral ankle radiograph with radiopaque ruler as references calibration during the procedure to reduce digital discrepancy during measurement in PACS. Out of 68 subjects 39 % are male (from 20-61 years old) and 61 % are female (from 20-54 years old). Four variables were taken as calcaneus measurements that are MaxL, MaxH, BH and LaL. Mean and SD of the variables was calculated. Univariate and multivariate regression equation were derived from all these four calcaneus measurement. Results Most of the calcaneus measurement had correlation with height (p < 0.05) with range of 0.166 to 0.528 for male and 0.274 to 0.654 for female. The study shows multivariable equation has higher or equal correlation with univariate equation. However in this study univariable shows smaller SEE compare to the multivariate which shows univariable has more accuracy in estimation stature. Conclusions Calcaneus measurement can provide reliability in estimation of stature of an individual. With the additional factors from multivariable, the accuracy of estimating stature from the calcaneus measurement will be as good as long bone.